2016
DOI: 10.1186/s12889-016-2836-0
|View full text |Cite
|
Sign up to set email alerts
|

The extended Infant Feeding, Activity and Nutrition Trial (InFANT Extend) Program: a cluster-randomized controlled trial of an early intervention to prevent childhood obesity

Abstract: BackgroundUnderstanding how we can prevent childhood obesity in scalable and sustainable ways is imperative. Early RCT interventions focused on the first two years of life have shown promise however, differences in Body Mass Index between intervention and control groups diminish once the interventions cease. Innovative and cost-effective strategies seeking to continue to support parents to engender appropriate energy balance behaviours in young children need to be explored.Methods/DesignThe Infant Feeding Acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 55 publications
(58 reference statements)
0
57
0
1
Order By: Relevance
“…These barriers appear consistent with the strategies and skills parents reported they would be interested in developing. To date, current early child feeding interventions have included components such as positive parenting (encouragement of autonomy, warmth and self‐efficacy—as the strongest predictor of health behaviours and an inhibitor of barriers), as relevant to overcoming child tantrums, however, less attention appears to be given to supporting parents overcome food utilisation barriers such as time, money and grocery shopping skills . Future child feeding intervention are likely to benefit by framing curriculum to address these barriers, particularly in low socioeconomic and populations outside of capital cities.…”
Section: Discussionmentioning
confidence: 99%
“…These barriers appear consistent with the strategies and skills parents reported they would be interested in developing. To date, current early child feeding interventions have included components such as positive parenting (encouragement of autonomy, warmth and self‐efficacy—as the strongest predictor of health behaviours and an inhibitor of barriers), as relevant to overcoming child tantrums, however, less attention appears to be given to supporting parents overcome food utilisation barriers such as time, money and grocery shopping skills . Future child feeding intervention are likely to benefit by framing curriculum to address these barriers, particularly in low socioeconomic and populations outside of capital cities.…”
Section: Discussionmentioning
confidence: 99%
“…Several technologies may be involved, such as email (Bragadóttir, 2008), Facebook parent group (Campbell et al, 2016;Gruver et al, 2016), chat rooms, forums, blogs, or discussion boards (Ewing et al, 2009;Martin et al, 2016). The common feature is that these groups are always mediated by a psychologist or a health professional that monitors the adequacy of messages and information and provides additional information or feedback when appropriate.…”
Section: Online Discussion Chat Rooms and Forumsmentioning
confidence: 99%
“…Details of these studies have been reported previously. [12][13][14] In brief, the Melbourne and Child Health Centers and randomised to intervention or control conditions. Intervention strategies included six dietitian-delivered group education sessions that included information on infant feeding, physical activity, and sedentary behaviours.…”
Section: Office For Children and The Department Of Education And Earlymentioning
confidence: 99%